Heidegger and the media - Gunkel, David J.; Taylor, Paul A. 1967- (Theory and media., 2014)
The most significant philosopher of Being, Martin Heidegger has nevertheless largely been ignored within communications studies. This book sets the record straight by demonstrating the profound implications of his unique philosophical project for our understanding of today's mediascape. The full range of Heidegger's writing from Being and Time to his later essays is drawn upon.